FRI0056 Altered Microrna Expression Pattern in Synovial and Blood Neutrophils in Rheumatoid Arthritis Reveals The Pathogenic Profile of These Cells. (15th July 2016) - Ruiz-Limon, P.; Perez-Sanchez, C.; Arias de la Rosa, I.; Jimenez-Gomez, Y.; Abalos-Aguilera, M.C.; Caracuel, M.A.; Font, P.; Ortega, R.; Calvo, J.; Castro, M.C.; Collantes-Estevez, E.; Escudero, A.; et al.
Abstract : Background: MicroRNAs (miRNA) have recently emerged as a new class of modulators of gene expression. Several studies have shown a deregulation of miRNAs in peripheral blood mononuclear cells or T lymphocytes, in synovial tissue and fibroblasts that might contribute to inflammation, degradation of extracellular matrix and invasive behavior of the resident cells in rheumatoid arthritis (RA). Neutrophils are key cells participating in the joint destruction. Objectives: To investigate the miRNA expression profile in synovial and blood neutrophils in RA and its role in the pathogenesis of this disorder. Methods: Neutrophils were isolated from peripheral blood of 20 healthy donors and 20 RA patients. Synovial neutrophils were isolated from paired synovial fluid of 10 RA patients. nCounter microRNA Assay was used to detect simultaneously 800 human microRNAs in each sample.100 ng of RNA from peripheral blood and synovial neutrophils were prepared by ligating a specific DNA tag (miR-tag) onto the 30 end of each mature microRNA according to the manufacturer's instructions. Altered miRNAs were analyzed for potential mRNA targets using Ingenuity pathways analysis (IPA) software. miRNA expression levels were validated through RT-PCR. Several mRNA targets of these miRNAs were analyzed by RT-PCR. Healthy neutrophils were treated in vitro with anti-CCPs isolated from RA patients. mRNA expression of DICER, Ago1, Ago2, exportin was evaluated through RT-PCR. DICER protein expression was analyzed by western blot. Results: Among 800 miRNAs analyzed, 121 were detected in neutrophils from peripheral blood or synovial fluid. Using a 2 fold change cut off, 97 miRNAs were altered in peripheral blood neutrophils from RA patients compared to healthy donors. Most of them were downregulated (94 downregulated and 3 upregulated). Accordingly, RA neutrophils showed a downregulation of the proteins participating in miRNA biogenesis, including DICER, Ago1, Ago2, exportin 5. In addition, treatment of healthy neutrophils with IgGs anti-CCPs isolated from RA patients decreased the expression of these proteins, thus pointing at these autoantibodies as main modulators of microRNA neutrophil expression. Functional IPA analysis showed that altered miRNAs regulated cellular functions such as development, growth, proliferation and movement and were mainly involved in immunological disease. Among the miRNAs found deregulated blood, 34 miRNAs were found even more significantly reduced in synovial neutrophils compared to paired blood neutrophils from RA patients. These miRNAs were mainly involved in inflammatory response, suggesting the abnormal activation of this cell subtype in the joint. Conclusions: 1) RA neutrophils exhibit a defect in the miRNAs processing, showed by a decrease in most of the detected miRNAs and the concomitant downregulation of proteins involved in their biogenesis. This defect seems to be modulated, at least partially, by anti-CCPs antibodies. 2) miRNA downregulation is even more pronounced in synovial resident neutrophils, which may contribute to the high inflammatory profile of these cells in the joint. Acknowledgement: Funded by CTS7940, PI2013–0191, CP15/00158, PI15/01333 Disclosure of Interest: None declared